Thomas Reid and the university - Wood, Paul; Broadie, Alexander (The Edinburgh edition of Thomas Reid, 2021)
Reid's ideas on education are a direct development of his theory of the mind, and the writings in this volume form an integral part of his philosophy that has, until now, been ignored.